Antecedents of Enterprise Resource Planning and its Impact on Firm Perfromance with Supply Chain Integration as Mediating factor - MUHAMMAD MOINUDDIN QAZI ABRO; ZAHID A. MEMON; ASIF ALI SHAH; IFFAT BATOOL NAQVI (Mehran University Research Journal of Engineering and Technology, 2017)
In today?s knowledge based globalized business world, the contemporary organizations are thriving to apply the innovative as well as modern business techniques and tools in their products and processes regularly. Besides, the organizations give sufficient significance while building up their business organisms and operations in order to utilize the innovative methodologies alongside their other primary procedures. Based on the ERP (Enterprise Resource Planning) and prior literature on management of supply chain, this paper analyzed an integrated model of ERP assimilation and integration by using Saudi Arabian firms as a case. This paper addresses the questions (1) there is a positive link between technological, organizational and environmental factors and ERP implementation, and (2) that ERP implementation encourages SCI (Supply Chain Integration) and performance. The paper empirically examines the antecedents of ERP implementation on SCI which will lead towards the firm performance by using SEM (Structural Equation Modeling) as an approach. Moreover, ERP is used as a mediating factor by using quantitative data, collected from Tadawul. Tadawul is Saudi Arabian stock exchange, in which 167 firms are registered. The results of the paper, may add to the hypothetical comprehension of accomplishing a change in supply chain management, and might leave some imperative implications for the firms motivated by enhancing their supply chain performance. It is also found that the linkage from ERP implementation to SCI is very significant.